Use of technological resources for the development of computational thinking following the steps of solving problems in engineering students recently entering college - Mamani Calcina, Jorge Gilbert (2023)
In this work, the authors propose the use of technological resources to develop computational thinking following the steps or phases of problem-solving for first-year students. During the development of the activities using technological resources (Arduino board, sensors, electronic devices, and mBlock) the students carried out activities, such as algorithm development and programming of the Arduino board and sensors from a friendly and playful interface such as the mBlock, as well as the debugging of programs until obtaining the expected results. These activities had an impact on the cognitive processes, practices, and technological perspectives of the students. Causality has been shown to exist between computational thinking skills and problem-solving phases in an environment of engineering students entering college. For the analysis of the relationship between computational thinking skills and problem-solving, Pearson’s statistical correlation test was used through SPSS software.